EDUKASI DAN OPERASIONAL DAPUR SEHAT ATASI STUNTING (DASHAT) KAMPUNG KELUARGA BERKUALITAS DESA BONEATIRO KABUPATEN BUTON: Education And Operations Of Healthy Kitchens Overcoming Stunting (Dashat) Quality Family Village, Boneatiro Village, Buton Regency - Nastia Nastia; Agustina Sarifudin; Nelvianti Nelvianti; Alan Umar; Imran Imran (Pakis Journal Institute, 2023)
The family is the first and foremost container for children's growth and development, including in handling nutrition, quality of sanitation, environment, access to education, health, and others. A healthy family itself is of course related to family food security which has an impact on fulfilling family nutrition and family health. Therefore it is necessary to educate the public regarding the processing of healthy kitchens to meet the nutritional needs of families by utilizing food security available in the local area, the purpose of education carried out through this community service activity is to achieve adequate family nutrition and avoid malnutrition. one of which can affect aspects of family health is stunting. The result of this activity is that people can choose cheap, quality, and healthy food ingredients and can process them to produce nutritious food menus. The location of activity was carried out in Boneatiro Village, Quality Family Village through the Healthy Kitchen Overcoming Stunting (DASHAT) program. This activity was centered by the Boneatiro Village Government, PKK Cadres, BKKBN Family Planning Extension, and Boneatiro Village Women.